Transnational modern languages a handbook - Burns, Jennifer; Duncan, Derek (Transnational modern languages, 2021)
In a world increasingly defined by the transnational and translingual, and by the pressures of globalisation, it has become difficult to study culture as primarily a national phenomenon. This book offers students across Modern Languages an introduction to the kind of methodological questions they need to look at culture transnationally. Each of the short essays takes a key concept in cultural study and suggests how it might be used to explore and illuminate some aspect of identity, mobility, translation, and cultural exchange across borders. The authors range over different language areas and their wide chronological reach provides broad coverage, as well as a flexible and practical methodology for studying cultures in a transnational framework.